The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1001/archsurg.1992.01420020045007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gut Decontamination Reduces Nosocomial Infections and Length of Stay but Not Mortality or Organ Failure in Surgical Intensive Care Unit Patients

Abstract: Suppression of the gut luminal aerobic flora to reduce nosocomial infections was tested in a prospective, randomized, double-blind, placebo-controlled clinical trial in patients in a surgical intensive care unit who had persistent hypermetabolism. Forty-six patients were randomized to receive either norfloxacin, 500-mg suspension every 8 hours, together with nystatin, 1 million units every 6 hours, or matching placebo solutions administered through a nasogastric tube within 48 hours of surgical intensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(39 citation statements)
references
References 18 publications
0
36
0
3
Order By: Relevance
“…This was not the case for the SDDtreated groups from the studies with either concurrent or historic controls. Moreover, this was not the case for the control groups of 5 (9,25,32,44,45) of the 12 studies with concurrent controls for which data were available. Interestingly, the patterns of the pathogens in both the treated and the control groups of four of five of these concurrent controlled SDD studies (9,25,32,44) were unusual because of the high degree of identity, with at least 50% of isolates of the two groups being the same for each of these four studies.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This was not the case for the SDDtreated groups from the studies with either concurrent or historic controls. Moreover, this was not the case for the control groups of 5 (9,25,32,44,45) of the 12 studies with concurrent controls for which data were available. Interestingly, the patterns of the pathogens in both the treated and the control groups of four of five of these concurrent controlled SDD studies (9,25,32,44) were unusual because of the high degree of identity, with at least 50% of isolates of the two groups being the same for each of these four studies.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, this was not the case for the control groups of 5 (9,25,32,44,45) of the 12 studies with concurrent controls for which data were available. Interestingly, the patterns of the pathogens in both the treated and the control groups of four of five of these concurrent controlled SDD studies (9,25,32,44) were unusual because of the high degree of identity, with at least 50% of isolates of the two groups being the same for each of these four studies. For example, at least 50% of respiratory pathogens in both the SDD and the control groups in one study (32) were Staphylococcus aureus or, in another study (9), were either Candida spp.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies to date have not shown a statistically significant effect of SDD on length of ICU stay. However, a reduction of 2-3 days was apparent in several studies [3,31,47,53].…”
Section: Trials Of Sdd In Icumentioning
confidence: 98%
“…[2][3][4] Belgian and Austrian randomized controlled trials 3,4 have demonstrated that the classical selective intestinal decontamination regimen of polymyxin and tobramycin does cover nonfermenting gram-negative bacilli (apart from Enterobacteriaceae). 5 The partial efficacy of selective intestinal decontamination with fluoroquinolones can be explained by the observation that fluoroquinolones eradicate gut overgrowth of Enterobacteriaceae after intestinal excretion via the gut mucosa 6 but not the overgrowth of nonfermenting gram-negative bacilli, which is subsequently followed by polyclonality and resistance.…”
mentioning
confidence: 99%